RETRACTED: The role of environmental education in formation of environmental literacy of society - Ushakov Dmitry; Olexiva Victoria (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001